Ribosomal RNA gene sequencing for early diagnosis of Blastomyces dermatitidis infection - Sejal Morjaria; Caitlin Otto; Andre Moreira; Romy Chung; Vaios Hatzoglou; Manju Pillai; Niaz Banaei; Yi-Wei Tang; Cesar J. Figueroa (International Journal of Infectious Diseases, 2015)
Prompt detection and identification of fungal pathogens at the genus and species level is critical in order to provide timely antifungal therapy. Here, we highlight the vital role of molecular diagnostics in achieving a fast and definitive diagnosis of disseminated blastomycosis in a diabetic patient presenting as a brain mass initially thought to be tumoral in nature. A broad-range PCR amplification and sequencing of the fungal ribosomal RNA genes on brain biopsy tissue obtained during elective craniotomy revealed a final microbial identification of Ajellomyces dermatitidis (telemorph of Blastomyces dermatitidis).